2018
DOI: 10.1016/j.ypmed.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Internet little cigar and cigarillo vendors: Surveillance of sales and marketing practices via website content analysis

Abstract: Federal bans on flavored cigarettes and restrictions on age verification, payment, and shipping for Internet tobacco sales should be extended to include LCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Internet searches and simulated orders conducted in this study provide new insights into the compliance status of online ENDS vendors in the context of a comprehensive statewide ENDS sales ban that was enacted by Executive Order in Massachusetts for a period of approximately 3 months. Generally, age verification results align with other studies that either detected no age verification process on websites, using strategies that cannot effectively verify age, and only one that used a form of online age verification services 19 , 22 , 24 . Findings also augment prior policy and compliance studies that have identified state legislation banning direct-to-consumer shipments of internet/mail-order cigarette sales, instituting minimum age requirements, establishing vendor licensure requirements, requiring product safety requirements on online vaping/e-liquid product sales, implementing tax collection/remittances, and creating penalties and enforcement mechanisms (including against shippers, purchasers and vendors) 25 - 27 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Internet searches and simulated orders conducted in this study provide new insights into the compliance status of online ENDS vendors in the context of a comprehensive statewide ENDS sales ban that was enacted by Executive Order in Massachusetts for a period of approximately 3 months. Generally, age verification results align with other studies that either detected no age verification process on websites, using strategies that cannot effectively verify age, and only one that used a form of online age verification services 19 , 22 , 24 . Findings also augment prior policy and compliance studies that have identified state legislation banning direct-to-consumer shipments of internet/mail-order cigarette sales, instituting minimum age requirements, establishing vendor licensure requirements, requiring product safety requirements on online vaping/e-liquid product sales, implementing tax collection/remittances, and creating penalties and enforcement mechanisms (including against shippers, purchasers and vendors) 25 - 27 .…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have conducted content analysis of online ENDS and tobacco vendors to identify vendor characteristics (e.g. location, types of online stores, payment processes, shipping options), product offerings and pricing, marketing strategies, age verification processes, use of social media, and health claims made but not in the context of a comprehensive sales ban that covers all ENDS products [17][18][19][20][21][22][23] . Building on these prior studies this study conducted structured web surveillance and simulated purchases to specifically characterize compliance of online ENDS vendors to the state sales ban and identify characteristics of domestic and international vendors by using IP addresses and other website information.…”
Section: Introductionmentioning
confidence: 99%
“…We identified IEVs from a concurrent study of the practices of ITVs selling all types of tobacco products. 27 We used several sources to identify potential ITVs, as described in figure 1 depicting study sampling sources and procedures.…”
Section: Methodsmentioning
confidence: 99%
“…A content analysis of online tobacco vendor websites indicated that the majority of online e-cigarette vendors are US based and sell flavored products ( Williams et al, 2018 ), a major concern for both youth access and youth appeal. Furthermore, more than half of online vendors were found to use ineffective age verification or no verification at all before purchase ( Williams and Derrick, 2018 , Williams et al, 2018 ). In 2019, industry analysts estimated that online retailers for e-cigarettes comprised 19% of the e-cigarette market ( Herzog, 2019 ).…”
Section: Discussionmentioning
confidence: 99%